Iron-catalysed hydroboration of non-activated imines and nitriles: kinetic and mechanistic studies. Issue 25 (23rd April 2021) - Bazkiaei, Adineh Rezaei; Wiseman, Michael; Findlater, Michael
Abstract : Iron-catalysed hydroboration of imines and nitriles has been developed under low catalyst loading (1 mol%) in the presence of HBpin. Abstract : Iron-catalysed hydroboration of imines and nitriles has been developed under low catalyst loading (1 mol%) in the presence of HBpin. A wide scope of substrate was found to smoothly undergo hydroboration, including electron releasing/withdrawing and halogen substitution patterns and cyclic substrates which all afforded the corresponding amines in good to excellent yields. Dihydroboration of nitriles was achieved conveniently under solvent free and additive free conditions. Promisingly, this catalytic system is also capable of the hydroboration of challenging ketimine substrates. Preliminary kinetic analysis of imine hydroboration reveals a first-order dependence on catalyst concentration. Both HBpin and 4-fluorophenyl- N -phenylmethanimine (1b ) appear to exhibit saturation kinetics with first order dependence up to 0.5 mmol HBpin and 0.75 mmol imine, respectively. Temperature-dependent rate experiments for imine hydroboration have also been explored. Activation parameters for the hydroboration of F PhCNPh (1b ) were determined from the Eyring and Arrhenius plots with Δ S ≠, Δ H ≠, and E a values of −28.69 (±0.3) e.u., 12.95 (±0.04) kcal mol −1, and 15.22 (±0.09) kcal mol −1, respectively.